Upaya Pencegahan Praktik Jual Beli Jabatan: Mewujudkan Birokrasi Bersih dan Bebas Korupsi di Lingkungan Pemerintah Daerah - Rizal Rizqi Ramadhan; Sulistyanta Sulistyanta (Lembaga Pengembangan Kinerja Dosen, 2025)
Corruption, particularly in the form of the practice of selling and buying positions, has become a serious issue in the context of regional governance in Indonesia. It undermines the meritocratic system and erodes public trust in government institutions. The aim of this study is to identify the factors that contribute to the occurrence of position trading and to formulate effective prevention strategies to build a transparent and corruption-free bureaucratic system. The approach used in this research is a normative approach with legal document analysis and field research that is prescriptive and applied in nature. The findings of the study show that the high political costs in direct regional elections and the lack of transparency in the selection of positions are the main factors triggering the practice of position trading. Prevention can be achieved through strengthening the merit system, improving transparency, fostering a culture of integrity in the bureaucracy, and enhancing the protection system for whistleblowers. The implications of this research are the importance of a more effective preventive approach to corruption prevention and the need for tighter public oversight to ensure the consistent implementation of policies.